2016
DOI: 10.1051/0004-6361/201527053
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in a solar quiet region and the influence of the magnetic canopy

Abstract: Aims. We seek indications or evidence of transmission/conversion of magnetoacoustic waves at the magnetic canopy, as a result of its impact on the properties of the wave field of the photosphere and chromosphere. Methods. We use cross-wavelet analysis to measure phase differences between intensity and Doppler signal oscillations in the Hα, Ca ii h, and G-band. We use the height of the magnetic canopy to create appropriate masks to separate internetwork (IN) and magnetic canopy regions. We study wave propagatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Abbasvand et al(2020b) concluded that the flux contained in magneto-acoustic waves with frequencies up to 20 mHz is sufficient to balance the radiative losses of the quiet chromosphere up to 1000-1400 km height. The difference with the previous results can be attributed to the existence of magnetic shadows (areas with reduced wave power at a given frequency), which prevents part of the acoustic energy reaching chromospheric heights in the network and plage regions, similar to observations by Kontogiannis et al (2014Kontogiannis et al ( , 2016. It is worth noting that the quiet-Sun magnetic network elements are surrounded by such a "magnetic shadows" (McIntosh and Judge 2001), which are the regions that lack oscillatory power at higher frequencies.…”
Section: Wave Heating Of the Large-scale Chromospheresupporting
confidence: 55%
See 1 more Smart Citation
“…Abbasvand et al(2020b) concluded that the flux contained in magneto-acoustic waves with frequencies up to 20 mHz is sufficient to balance the radiative losses of the quiet chromosphere up to 1000-1400 km height. The difference with the previous results can be attributed to the existence of magnetic shadows (areas with reduced wave power at a given frequency), which prevents part of the acoustic energy reaching chromospheric heights in the network and plage regions, similar to observations by Kontogiannis et al (2014Kontogiannis et al ( , 2016. It is worth noting that the quiet-Sun magnetic network elements are surrounded by such a "magnetic shadows" (McIntosh and Judge 2001), which are the regions that lack oscillatory power at higher frequencies.…”
Section: Wave Heating Of the Large-scale Chromospheresupporting
confidence: 55%
“…The wave energy transport is extensively studied in observations. A number of studies points that the mode transformation mechanism is indeed acting in the Sun (Moretti et al 2007;Rajaguru et al 2013Rajaguru et al , 2019Kontogiannis et al 2014Kontogiannis et al , 2016Grant et al 2018). In particular, one of the most prominent phenomena that is now believed to be essentially due to the mode transformation is the presence of high frequency acoustic halos surrounding active regions (Khomenko and Collados 2009;Rijs et al 2016).…”
Section: Wave Heating Of the Large-scale Chromospherementioning
confidence: 99%
“…The acoustic waves undergo the mode conversion of magnetoacoustic waves on equipartition surfaces in the upper photosphere, where the Alfvén velocity is equal to the sound speed. The inclined magnetic field then also facilitates the propagation of the waves with frequencies below the acoustic cut-off frequency ν ac = 5.2 mHz (Bel & Leroy 1977) into the upper atmosphere through so-called magnetic portals (Jefferies et al 2006;Stangalini et al 2011;Kontogiannis et al 2014Kontogiannis et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Waves have been recognized as important contributors to chromospheric heating, although their heating mechanisms are elusive (see Jess et al 2015, for a review). While the propagation of waves in the chromosphere has been well studied from both the observational and theoretical perspectives (e.g., Bogdan et al 2003;Hasan & Ulmschneider 2004;Hasan et al 2005;Hasan & van Ballegooijen 2008;Vigeesh et al 2009;Heggland et al 2011;Vigeesh et al 2012;de la Cruz Rodríguez et al 2013;Kontogiannis et al 2016;Santamaria et al 2016;Kayshap et al 2018;Abbasvand et al 2020), a firm quantitative conclusion is still a distance away.…”
Section: Introductionmentioning
confidence: 99%